Pre-Mongol Exegetical Hymnography. Part 1: The Canon for the Feast of the Cross (Publication of a Source) - Temčinas, Sergejus (Senoji Lietuvos literatūra, 2026)
This is a publication of an exegetical canon for the Feast of the Cross from a pre-Mongol set of original (untranslated) exegetical canons (dated approximately 1170–1180) for ten ecclesiastic feast days of the Menaion and Triodion cycles. This set originated in Kievan Rus’ and was widely distributed in East Slavonic manuscript tradition. It was also known in the Grand Duchy of Lithuania, where the exegetical canon for Easter was even translated into the Ruthenian language (the author of this article published it in 2020). Based on a combination of linguistic, content-related, and intertextual features, this anonymous set of exegetical canons has been attributed to the Jerusalem monk Afanasii (who did indeed live in the Holy Land for some time), known as the author of his ‘Epistle to Panko about the Wood of the Holy Cross’ and the commentator on the ‘Epistle by Kliment Smoliatich [Metropolitan of Kiev from 1147 to 1155 – S. T.] to the Smolensk Presbyter Foma’. Despite its widespread use in the manuscript tradition, the set has not been studied and remains virtually unknown to scholars. This publication is based on one of the very few manuscript copies containing the maximum number of texts from this cycle (ten out of twelve): Exegetical Psalter with additions from the early seventeenth century (Novosibirsk, State Public Scientific and Technical Library of Russia, collection of Mikhail Nikolaevich Tikhomirov, No. 41, f. 67–186v.).